RANCANG BANGUN BOOST CONVERTER PADA MINIATUR TURBIN ANGIN - Nugraha, Dimas Aji; Mudjirahardjo, Panca; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
In the development of electronic devices today, it greatly helps in the advancement of increasingly sophisticated technologies, one of which is power electronic converters that have various applications such as buck converter, boost converter, buck-boost converter, etc. A boost converter is an electronic device that can convert AC to AC, AC to DC, DC to AC, and DC to DC by increasing the electrical voltage towards the predetermined target. In terms of the development of boost converter applications, they are widely found in renewable energy technologies such as solar, wind, water, geothermal, etc, which function as auxiliary devices to increase the voltage from the energy source to the storage location. In this research, a DC-DC boost converter will be designed for a miniature wind turbine with an input operating voltage of 3-7 volts and a desired output voltage target of around 12-13 volts, which will then be applied to charge a 12V 5AH battery. Keywords : Boost Converter, Renewable Energy, Miniature Wind Turbine, Battery Charging.